PENGARUH E-SERVICE QUALITY DAN E-TRUST TERHADAP REPURCHASE INTENTION MELALUI E-SATISFACTION PADA E-COMMERCE BUKALAPAK DI KOTA BANDUNG - Febriana, Cintia Fina; Leni Evangalista (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research is aimed at examining the influence of e-servqual and on repurchase intention, mediated by e-satisfaction, among users of the Bukalapak E-commerce application in the city of Bandung. The study involves 120 respondents who are users of the Bukalapak E-commerce application. Data collection is conducted through the distribution of an online questionnaire, and the time horizon used to collect relevant data is a one-shot study or cross-sectional approach. The research instrument has undergone stages of validity and reliability testing, classical assumption testing, and multiple regression testing. The data analysis tool used for instrument testing is the SPSS software version 26 and the Sobel test. This study comprises seven hypotheses, with the research findings indicating that e-servqual and e-trust have a positive and significant impact on e-satisfaction. Additionally, both e-servqual and e-trust also exhibit a positive and significant influence on repurchase intention. Furthermore, e-satisfaction demonstrates a positive and significant impact on repurchase intention. Subsequently, e-customer satisfaction successfully mediates the influence of e-servqual and e-trust on repurchase intention.